Specification and control synthesis for networked vehicle systems - J. Borges de Sousa (2003)
A framework for the representation, formal specification, and control synthesis for networked vehicle systems is presented. From dynamic optimization, this framework has inherited the concepts and theories of optimality, reach set computation and control, and the motivation to improve the performance of increasingly complex physical processes. From set theory, this framework borrowed the representational power of the language of sets to capture the relations among vehicles and controllers in a way that is consistent with control design. The ANTEX-M project is described to illustrate the challenges posed by networked vehicle systems and to illustrate how the framework addresses these challenges.